Kultina VS. Quality of life as a factor of economic security of regions in Central Federal District for the period 2021–2022 - A. Yu. Fedorova; E. V. Weiss; M. V. Ilyukhina; V. S. Kultina (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. At present, economic security is the main indicator of the quality of life of the population of our country in the context of the spatial development of the economy. The article is devoted to the actual problem of the regions today – the assessment of the standard of living of the population.Goal. The main goal set by the authors when writing the article is to assess the standard of living of the population of the regions of the Central Federal District, using a variety of statistical indicators, as well as analyzing the socio-economic factors that affect the well-being of citizens.Materials and methods. All calculations are made on the basis of official data from the Federal State Statistics Service and statistical collections of the socio-economic situation.Results and discussion. The survey conducted in the form of a questionnaire poll of citizens of the Central Federal District made it possible to form an idea of the structure of the quality of life of the population of the district. Further analysis of the main quantitative and qualitative indicators of the standard of living of the population of the regions made it possible to conclude about the socio-economic situation in the district under consideration. The practical significance of the study lies in the possibility of using the results of the study by the regions of the Central Federal District in the development and formation of a strategy for socio-economic development in order to improve the level and quality of life of the population.Conclusion. Based on the results of the study, it can be concluded that in the Central Federal District there was an improvement in the quality of life of the population in 2022 compared to 2021. The conclusion is made about the relationship between the level and quality of life of the population with inflationary processes, and the demographic situation of the district at the present time, which has a direct impact on the socioeconomic situation of the analyzed regions, is noted.